IL-17RA receptor signaling contributes to lung inflammation and parasite burden during Toxocara canis infection in mice - Leal-Silva, Thaís; Lopes, Camila de Almeida; Vieira-Santos, Flaviane; Oliveira, Fabrício Marcus Silva; Kraemer, Lucas; Padrão, Luiza de Lima Silva; Amorim, Chiara Cássia Oliveira; Souza, Jorge Lucas Nascimento; Russo, Remo Castro; Fujiwara, Ricardo Toshio; Magalhães, Luisa Mourão Dias; Bueno, Lilian Lacerda (Frontiers in Immunology, 2022)
IL-17 is a cytokine produced by innate and acquired immunity cells that have an action against fungi and bacteria. However, its action in helminth infections is unclear, including in Toxocara canis infection. Toxocariasis is a neglected zoonosis representing a significant public health problem with an estimated seroprevalence of 19% worldwide. In the present study, we describe the immunopathological action of IL-17 in acute T. canis infection. C57BL/6j (WT) and IL-17RA receptor knockout (IL-17RA-/-) mice were infected with 1000 T. canis eggs. Mice were evaluated 3 days post-infection for parasite load and white blood cell count. Lung tissue was harvested for histopathology and cytokine expression. In addition, we performed multiparametric flow cytometry in the BAL and peripheral blood, evaluating phenotypic and functional changes in myeloid and lymphoid populations. We showed that IL-17 is essential to control larvae load in the lung; however, IL-17 contributed to pulmonary inflammation, inducing inflammatory nodular aggregates formation and higher expression of IL-6 locally. The presence of IL-17 was associated with a higher frequency of neutrophils as a source of IL-4 and IL-17 in BAL, while in the absence of IL-17RA, mice display a higher frequency of alveolar macrophages expressing the same cytokines. Systemically, IL-17 reduced the frequency of activated eosinophils expressing IL-4 and IL-17. Taken together, this study indicates that neutrophils may be an important source of IL-17 in the lungs during T. canis infection. Furthermore, IL-17 is essential to control parasite load, however, its presence triggers lung inflammation and tissue damage.